An international physical activity and public health research agenda to inform COVID-19 policies and practices - Sallis, J. F.; Adlakha, D.; Oyeyemi, A.; Salvo, D. (Journal of Sport and Health Science, 2020)
We encourage investigators from around the world to conduct studies like those recommended here and to initiate them as soon as possible. Ideally, investigators could coordinate their study methods, measures, and analyses so results across countries will be as comparable as possible. This is scientifically important so country-context similarities and differences can be documented and distinguished from methodological differences. To facilitate coordination of studies across sites, we created a repository of PA and COVID-19 research studies that supports researchers with similar interests to connect ( https://forms.gle/rZ9k4TNruSVnpKiv9 ). We invite PA researchers, scientific organizations, and global scientific networks to disseminate and contribute to this repository.